Evaluasi Program Inaugurasi HIMA Tekpend Mengunakan Model CIPP - Kamila, Syifa Asri; Cucu Sukmana (Universitas Negeri Surabaya, 2025)
Abstract:This study aims to evaluate the program to see how successful the Hima Tekpend Inauguration program has been. The evaluation of this inauguration program has the aim of staying in touch between the families of Tekpend students, where the inauguration program for class of 2021 takes the theme FAMOLOKA. The method used in this study is a qualitative approach, in which research produces descriptive data. Then the evaluation model used is the CIPP model, choosing to use this model because it can guide and evaluate a program from all sides, namely from the planning process, concept, subject and object. So that the results and discussion in this study show that the context, input, processes and products of the inauguration program are good as planned and resulted in the familiarity between the generations that was obtained from the inauguration program. Keywords: Inauguration, Program Evaluation, CIPP Evaluation Model